ENHANCING THE SOLUBILITY OF DIPYRIDAMOLE BY LIQUISOLID COMPACTS BASED ON A FACTORIAL DESIGN APPROACH (Journal of Pharmaceutical Negative Results, 2022)
Dipyridamole is a phosphodiesterase inhibitor used to prevent postoperative thromboembolic events. It is a poorly water-soluble drug with absolute bioavailability of 37-66 %. Water-insoluble drugs still have a poor dissolution rate, one of the biggest problems facing the pharmaceutical industry. To improve the dissolution rate of Dipyridamole, liquisolid compacts were developed in the present study. Liquidsolid formulations were prepared using Peceol, Avicel PH 112, and Aerosil, in different ratios, as a non-volatile solvent, carrier material and coating material respectively. Excipients and drug interactions were characterized through FT-IR. These studies showed no interaction between excipients and drug. 32 factorial design approach was implemented. The formulations were optimized using Design Expert version 13.00 (StatEase Inc., Minneapolis, MN, USA). An optimal formulation exhibited an angle of repose of 25.12°, a hardness of 3.1 kg/cm2 and a percentage cumulative drug release of 99.22 % after 10 minutes. The observed values were found to be similar to the predicted values. Based on these observations, DPY–O can be considered to be the optimum formulation.